Splenic contraction and cardiovascular responses are augmented during apnea compared to rebreathing in humans - Persson, Gustav; Lodin-Sundström, Angelica; Linér, Mats H.; Andersson, Samuel H. A.; Sjögreen, Bodil; Andersson, Johan P. A. (Frontiers in Physiology, 2023)
The spleen contracts during apnea, releasing stored erythrocytes, thereby increasing systemic hemoglobin concentration (Hb). We compared apnea and rebreathing periods, of equal sub-maximal duration (mean 137 seconds), in eighteen subjects to evaluate whether respiratory arrest or hypoxic and hypercapnic chemoreceptor stimulation is the primary elicitor of splenic contraction and cardiovascular responses during apnea. Spleen volume, Hb, cardiovascular variables, arterial (SaO2), cerebral (ScO2), and deltoid muscle oxygen saturations (SmO2) were recorded during the trials and end-tidal partial pressure of oxygen (PETO2) and carbon dioxide (PETCO2) were measured before and after maneuvers. The spleen volume was smaller after apnea, 213 (SD 89) ml, than after rebreathing, 239 (95) ml, corresponding to relative reductions from control by 20.8 (17.8) % and 11.6 (8.0) %, respectively. The Hb increased 2.4 (2.0) % during apnea, while there was no significant change with rebreathing. The cardiovascular responses, including bradycardia, decrease in cardiac output, and increase in total peripheral resistance, were augmented during apnea compared to during rebreathing. The PETO2 was higher, and the PETCO2 was lower, after apnea compared to after rebreathing. The ScO2 was maintained during maneuvers. The SaO2 decreased 3.8 (3.1) % during apnea, and even more, 5.4 (4.4) %, during rebreathing, while the SmO2 decreased less during rebreathing, 2.2 (2.8) %, than during apnea, 8.3 (6.2) %. We conclude that respiratory arrest per se is an important stimulus for splenic contraction and Hb increase during apnea, as well as an important initiating factor for the apnea-associated cardiovascular responses and their oxygen-conserving effects.